(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
The rising global market for construction has resulted in an increase in the usage of concrete. On the other hand, traditional concrete-making materials are not totally ecologically friendly, driving research towards greener concrete alternatives. Agricultural wastes including those from biodiesel production, coconut, sorghum, and the paddy sector have been extensively studied in the past, and the results demonstrate that such materials would be used in construction. Repurposing agricultural by - products materials in the construction might reduce dependence on traditional cement resources while also lowering impact on the environment, waste management, and sewage disposal. This article examines the usage of producing alternative farming waste cementitious materials, including such bamboo, cornmeal, wheat, olive, rattan, seashell, and other substances, with the purpose of evaluating the positives and cons of doing so. The employment of agricultural powder in concrete throughout various forms, such as partial anthracite or aggregate replacements, as well as fibre reinforcements, is investigated in this study. Despite the use of agricultural waste materials lowered specific concrete properties, the publication’s main conclusion is that effective therapeutic processes and judicious selection of materials should allow for the preparation of cement with enhanced performance. The review and discussion in this article should provide new knowledge and understanding of a broader range of agricultural residues that could be used to build greener, more responsible concrete.